The effects of targeted vagus nerve stimulation on glucose homeostasis in STZ-induced diabetic rodents - Dirr, Elliott W.; Patel, Yogi; Johnson, Richard D.; Otto, Kevin J. (Frontiers in Neuroscience, 2023)
Pancreatic β-cells are neuroresponsive endocrine cells that receive input from the vagus nerve. This neural pathway can be utilized as a point of therapeutic intervention by delivering electrical stimulation. To minimize off-target effects, neuromodulation of exclusively β-cells can be achieved by careful anatomical placement of an extraneural interface around a nerve just prior to pancreatic insertion. This targeted approach was utilized to chronically modulate β-cells in a type 1 diabetic rat model without systemic changes to heart or respiratory rate. We hypothesized that targeted pancreatic vagus nerve stimulation (pVNS) would lower blood glucose by driving surviving β-cells to secrete insulin. We found increased circulating insulin coinciding with changes in blood glucose concentration. This effect was temporally specific to the application of stimulation. We did not observe increased pancreatic perfusion, which suggests that modulation of blood glucose was due to activation of β-cells rather than changes to extra-organ transport of insulin.